PRAKTIK IDENTITAS KELAS DALAM STIKER KOTA - Jejen Jaelani (Jurnal Sosioteknologi, 2009)
Town sticker phenomenon has been appeared long time ago. This phenomenon happened without any serious purpose. At the beginning, it functioned only as a decoration. Gradually, along with the development of people thought, point of view, and the increase of their taste, the function of sticker changes. Nowadays, town stickers become a practical media of social class identity. Then such phenomenon is being observed by critical discourse analysis (AWK). Based on that analysis, town sticker has become effective media to show class identity of their owner.